Discourses of Legal Certainty in Execution of Administrative Court Decision - Nyoman Martana; Putu Ade Hariestha Martana; Kadek Agus Sudiarawan; Bagus Hermanto (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2019)
After the enactment of the Law of Government Administration implied the regulation concerning the execution of the Administrative Court Judgment. Some pro-cons academic and practice discourses, arguing that the enactment of the Law of Government Administration is the culminating point from the limited role of the Administrative Court on enforcing the administrative law and the argument that the regulation of the Law of Government Administration contains various ambiguities norms in concern with implementation in the Administrative Procedural Law System. This study aims to analyze and discuss concerning the regulation of the provisions of the Administrative Court Ruling execution, constrains in judgment execution and the legal certainty for the justice seekers in the provisions of the Administrative Court Ruling execution after the enactment of the Law of Government Administration. This paper is using a normative and empirical method. The data that using consisted of primary and secondary data, were analyzed using qualitative methods. This study result is presented in a descriptive analysis paper.